Das "Janusgesicht" der Menschenwürde Regulierung im Spannungsfeld von Medienrecht und Medienethik - Erdemir, Murad (Universitätsverlag Göttingen, 2014)
This book documents the inaugural public lecture of Honorary Professor Dr. Murad Erdemir, held on May 28th 2014 in the auditorium of the University of Göttingen. Murad Erdemir is the Vice Director and General Counsel in the Hessian State Authority for Commercial Broadcasting and New Media (LPR Hessen). His inaugural lecture looks at human dignity as a central concept of law and ethics. The lecture covers the media law review and also the supervisory practices of the State Media Authorities and the German Press Council. The full text is reprinted, also including references and further reading.